Amood Al-Sher In Arabic Literature The Elegy Of Abu Al-Ala Al-Ma'arri For His Mother - Al-Saedi, Saleh Salem (Ijaz Arabi Journal of Arabic Learning, 2023)
The research describes the systematic development of Arab critical theory in Arab heritage. This research applies Al-Marzuqi's 'Amood al-Sher' theory to the elegy penned by Abu al-Ala Al-Ma'arri for his mother. The methodology follows the distribution of Al-Marzuqi's seven articles for the 'Amood al-Sher' and its application to Abu al-Ala Al-Ma'arri's elegy for his mother. This research also examines an ideology on the possibilities of creativity in ancient Arab criticism despite numerous contradictory viewpoints. In addition, it makes a concerted effort to reconsider the "Amood al-Sher" theory to develop it, work on it, and thoroughly study it to foster originality in Arab criticism. The study concludes that Al-Ma'arri's "elegy" met the conditions for "Amood al-Sher." In addition, the possibilities of generalizing this theory to the Arabic poem to develop its rhetorical and literary innovation. These seven portions or points and their respective academic and intellectual standards illustrate the poem's inventiveness.